Integrated nutrient management to improve soil health, nutrient uptake and growth of Poplar (Populus deltoides) seedlings in nursery conditions - Khipla, Neha; Kaur, Jupinder; Gosal, S.K.; Gill, R.I.S.; Walia, S.S. (Indian Journal of Agroforestry, 2021)
Agricultural sustainability can never be achieved until dependence on chemicals for soil fertilization is reduced. Integrated nutrient management is a step towards sustainable management of soil, where optimum nutrition is provided to plants through integration of nutrient sources. This study was aimed to evaluate the combinations of inorganic fertilizers (75 and 100% of recommended N and P fertilizers) and biofertilizers (PSB, Azotobacter and consortium) to influence soil chemical properties, nutrient uptake and growth of poplar (clone PL-5) in nursery conditions. All the observed parameters (except soil pH) were found significantly (p